3D modeling of multimode and single mode fiber - Murizah Kassim; Ahmad Syahir Arif Mohd Zaid; Azlina Idris; Shahrani Shahbudin; Roslina Mohamad; Cik Ku Haroswati Che Ku Yahaya (Institute of Advanced Engineering and Science, 2019)
This paper presents a design of 3D modeling of Multimode and Single Mode Fiber using SolidWorks. Fiber technology is essential that presents optical fiber is the fastest optical cable laid by Internet Service Providers in network communication. The current design of both fibers has less detail animation on technical specifications of light propagations and cladding. Thus, characterization difficulties occur between this two fiber optics cables. It also has less promotion in media publications such as 3D model design as guidance to users. This paper presents details on 3D modeling of multimode mode and single mode fiber specifications held in the industry market. A 3D design with SolidWorks and comparison of both fiber characteristics are presented. Based on the 3D designed model, users are analyzed on their perspective and searching information which benefits telecommunication’s company. Technical calculations like core-cladding diameter ratio in microns are animated. The propagation of light in 3D single mode and multimode fiber is simulated using SolidWorks animator that presents it real fiber conditions. Result presents 10 most country searching used of both fiber cables and the difference in users search for both cables. A number of user’s search presents 3% more of multimode than single mode fiber search cases. This research is significant in presenting an animator of single and multimode fiber to users of network infrastructure development especially network developers and Telecommunications Company which can present it lively with animator transitions.